Contribution to the faunistics of shore bugs (Hemiptera: Heteroptera: Leptopodomorpha) in the Palaearctic Region and the Himalayas - Vinokurov, Nikolay N.; Kment, Petr (Zootaxa, 2015)
New distributional data on 33 species of the infraorder Leptopodomorpha (3 species of the family Leptopodidae and 30 species and subspecies of Saldidae) from the Palaearctic Region and Himalayas are provided. The following new or confirmed records are listed: Chartoscirta cocksii (Curtis, 1835) from Kosovo; Halosalda halophila (Jakovlev, 1876), Saldula amplicollis (Reuter, 1891) and Saldula xanthochila (Fieber, 1859) from Iran; Macrosaldula jakowleffi (Reuter, 1891) from Nepal and Pakistan; Macrosaldula scotica (Curtis, 1835) from Uzbekistan; Macrosaldula variabilis (Herrich-Schaeffer, 1835), Saldula lindskogi Vinokurov, 2004, Saldula opacula (Zetterstedt, 1838) from Afghanistan; Micracanthia ornatula (Reuter, 1881) from Oman; Saldula fucicola (J. Sahlberg, 1870) from Bosnia and Herzegovina and Bulgaria; Saldula lindbergi Lindskog, 1975 from Lebanon; Saldula melanoscela (Fieber, 1859) from Iran and Montenegro; Saldula palustris (Douglas, 1874) and Saldula pilosella hirsuta (Reuter, 1888) from Montenegro; Saldula orthochila (Fieber, 1859) from Afghanistan and Pakistan; Saldula pallipes (Fabricius, 1794) from Montenegro and Nepal; Saldula pilosella pilosella (Thomson, 1871) from Libya; and Saldula saltatoria (Linnaeus, 1758) from Iran and Nepal. A tabular checklist of Leptopodomorpha of Afghanistan, Iran and Pakistan is also provided.